2017
DOI: 10.18632/oncotarget.19964
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces acute bursal atrophy in broiler chicks by activating TLR4-MAPK-NF-κB/AP-1 signaling

Abstract: We investigated the mechanisms that induce atrophy of the chicken bursa of Fabricius (BF) upon lipopolysaccharide (LPS) treatment in young chicks. LPS treatment resulted in ∼36% decrease in bursal weight within 36 h (P < 0.01). Histological analysis showed infiltration of eosinophilic heterophils and nucleated oval shaped RBCs in or near blood vessels of the BF from LPS-treated chicks. Scanning electron micrographs showed severe erosion and breaks in the mucosal membrane at 12 h and complete exuviation of burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…(2000) and Ansari et al. (2017), that also reported that LPS challenge markedly reduced bursal weight in LPS-challenged broiler chickens compared to the control group. At the end of the experiment (day 35), there was no observed difference in the relative weight of the spleen, bursa, and liver between the different treatment groups.…”
Section: Discussionmentioning
confidence: 94%
“…(2000) and Ansari et al. (2017), that also reported that LPS challenge markedly reduced bursal weight in LPS-challenged broiler chickens compared to the control group. At the end of the experiment (day 35), there was no observed difference in the relative weight of the spleen, bursa, and liver between the different treatment groups.…”
Section: Discussionmentioning
confidence: 94%
“…GO functional classification on DEGs for each pair was conducted following the previously described method [25]. All GO terms are grouped into three ontologies: biological process, cellular component, and molecular function.…”
Section: Resultsmentioning
confidence: 99%
“…Following construction of strand-specific libraries, sequencing was done on an Illumina HiSeq 4000 platform by BGI Genomics Co. Ltd. (Shenzhen, China). Differentially expressed genes (DEGs) were screened using the NOISeq method with absolute fold change ≥ 2 and divergent probability ≥ 0.8 [24, 25]. The read length was 50 bp.…”
Section: Methodsmentioning
confidence: 99%
“…Monson et al [62] studied the effect of aflatoxin B1 and probiotics on turkey spleen transcriptome, and found that the expression level of DOCK10 had no significant different in the group of aflatoxin B1 and the group of probiotics compared with the control group, but it was significantly up-regulated in the group of aflatoxin B1+probiotics compared with the control group. Ansari et al [63] investigated the mechanisms that induce atrophy of the chicken bursa of fabricius upon lipopolysaccharide (LPS) treatment in young chicks, found that LPS treatment resulted in a significant decrease in the weight of bursa of fabricius, and the decrease of cell proliferation; at the same time, the DOCK10 was significantly up-regulated. This suggests that DOCK10 , as a proinflammatory factor, its high expression can induce abnormal apoptosis.…”
Section: Discussionmentioning
confidence: 99%